Forming of Lexical Competence of ElderPpreschool Children’s by Means of Poetic Works Of Ukrainian Writers - Kyrsta, Nataliya (Pedagogical Discourse, 2012)
The problems of forming of lexical competence of elder preschool children by means of poetic word are studied in the article. A didactics model is described and the studies standards of complex work after Mariyka Pidgirianka’s poetic works (in the aspect of dictionary development) are characterized. The pedagogical conditions and conformities of development of children’s vocabulary by facilities of poetic works are concretized.